Genomics, biotechnology and global health: the work of the University of Toronto joint centre for bioethics - Daar, Abdallah S.; Sahni, Puja; Singer, Peter A. (Acta Bioethica, 2004)
The new and rapidly advancing field of genomics and related biotechnologies has the ability to either improve or worsen global health inequities. In general, developing countries are left behind in the development of new technologies and advances in genomic medicine. In this view, the University of Toronto Joint Centre for Bioethics (JCB) through the Canadian Program on Genomics and Global Health has developed 25 research projects on capacity enhancement for developing countries for improving global health equity, including public health via genomics and related biotechnologies. One project with a great impact was the "Top Ten Biotechnologies for Improving Health in Developing Countries" for its influence in the "Grand Challenges in Global Health Initiative" foster by the Melinda Gates Foundation. Additionally, the UN Millennium Development Project has asked JCB to become the genomics working group for improving global health through genomics biotechnology and JCB has started by studying applications of genomics/biotechnologies in seven developing countries: Brazil, China, Cuba, Egypt, India, South Africa and South Korea, which may set examples for other developing nations.